2018
DOI: 10.1027/2192-0923/a000134
|View full text |Cite
|
Sign up to set email alerts
|

What’s Real About Virtual Reality Flight Simulation?

Abstract: Abstract. With the help of immersive virtual reality technology, novel cockpit systems can be evaluated with pilots in an early design phase. This comparative study investigates the functional fidelity of a virtual reality flight simulator (VRFS) in comparison with a conventional flight simulator. Pilots’ movement time to reach cockpit controls, deviation from the ideal flight path, workload, and simulator sickness are evaluated using an operational scenario. The results show statistically significant differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…The fact that NASA-TLX and SIM-TLX yielded no significant differences in subjective workload is inconsistent with the results of Oberhauser et al (2018) who reported a higher subjective workload in VR than conventional flight simulator using the NASA-TLX questionnaire. Kakkos et al (2019) found no effect of flight simulation interface (computer screen vs. VR) on subjective workload either, but did find an effect of the flight simulation interface on neurophysiologybased measures of workload (Kakkos et al, 2019).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The fact that NASA-TLX and SIM-TLX yielded no significant differences in subjective workload is inconsistent with the results of Oberhauser et al (2018) who reported a higher subjective workload in VR than conventional flight simulator using the NASA-TLX questionnaire. Kakkos et al (2019) found no effect of flight simulation interface (computer screen vs. VR) on subjective workload either, but did find an effect of the flight simulation interface on neurophysiologybased measures of workload (Kakkos et al, 2019).…”
Section: Discussioncontrasting
confidence: 71%
“…Despite this, a lack of performance between desktop and VR on tasks the require instrument flying demonstrates that the screen resolution of the employed VR system was suitable for reading the instruments (cf. Oberhauser et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The scenario was built with the HTC VIVE Pro eye VR headset as the main tool for delivery. The device was chosen for its ability to generate eye tracking data and its latency of less than 10ms in testing, a critical factor in immersive VR training (Oberhauser et al, 2018). The system was set up with two "base stations" that were located opposite to each other, which defined the space of the VR environment.…”
Section: Apparatusmentioning
confidence: 99%
“…Koglbauer et al [35] showed that flight performance could be significantly increased by simulator training using augmented cues, and addressed the potential use of AR cues for the pilots' orientation in the 3D space. Oberhauser et al [36] investigated the benefits and limitations of VR training and concluded that VR can partly be used to supplement simulator training.…”
Section: Theoretical Backgroundmentioning
confidence: 99%